Targeting Pdzrn3 maintains adult blood-brain barrier and central nervous system homeostasis. Issue 4 (April 2022) - Gueniot, Florian; Rubin, Sebastien; Bougaran, Pauline; Abelanet, Alice; Morel, Jean Luc; Bontempi, Bruno; Proust, Carole; Dufourcq, Pascale; Couffinhal, Thierry; Duplàa, Cecile
Blood brain barrier (BBB) disruption is a critical component of the pathophysiology of cognitive impairment of vascular etiology (VCI) and associated with Alzheimer's disease (AD). The Wnt pathway plays a crucial role in BBB maintenance, but there is limited data on its role in cognitive pathologies. The E3 ubiquitin ligase PDZRN3 is a regulator of the Wnt pathway. In a murine model of VCI, overexpressing Pdzrn3 in endothelial cell (EC) exacerbated BBB hyperpermeability and accelerated cognitive decline. We extended these observations, in both VCI and AD models, showing that EC-specific depletion of Pdzrn3, reinforced the BBB, with a decrease in vascular permeability and a subsequent spare in cognitive decline. We found that in cerebral vessels, Pdzrn3 depletion protects against AD-induced Wnt target gene alterations and enhances endothelial tight junctional proteins. Our results provide evidence that Wnt signaling could be a molecular link regulating BBB integrity and cognitive decline under VCI and AD pathologies.